Pengaruh Pertumbuhan Industri Kecil terhadap Keberlanjutan Pembangunan Kota Depok - Cholid, Sofyan (UI Scholars Hub, 2010)
Population growth along with standard of living and economic activity have affected the quality of the environment, such as quantity and quality of vehicles and Industries operating in the region. The imbalance between these three components, or emphasis on only one objective/component only resulted in failure in achieving sustainability in development. Considering the problems and constraints faced, as described in the previous section, this research examined the degree of sustainable development, and what will happen to Depok City in the future refers to existing pattern of development. This study used Sugeno-type Fuzzy Inference System with constant membership functions of the output, and works based on the rules set forth in the form of an IF-THEN statement. It was found that from 2001-2008. City of Depok reached the level of sustainability in three consecutive years, which are 2004, 2005, and 2006 It was characterized by good indicator of the settlement and industry area, the low frequency of catastrophic events, and the vast area of wetlands. Based on the model designed, the four conditions that occur in the three periods mentioned, and only at those periods Depok reached a level of sustainable development.